Detection potential of the KM3NeT detector for high-energy neutrinos from the Fermi bubbles - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Aharonian, F.; Aiello, S.; Albert, A.; Alexandri, M.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; et al. (Astroparticle Physics, 2013)
A recent analysis of the Fermi Large Area Telescope data provided evidence for a high-intensity emission of high-energy gamma rays with a E-2 spectrum from two large areas, spanning 50 above and below the Galactic centre (the "Fermi bubbles"). A hadronic mechanism was proposed for this gamma-ray emission making the Fermi bubbles promising source candidates of high-energy neutrino emission. In this work Monte Carlo simulations regarding the detectability of high-energy neutrinos from the Fermi bubbles with the future multi-km(3) neutrino telescope KM3NeT in the Mediterranean Sea are presented. Under the hypothesis that the gamma-ray emission is completely due to hadronic processes, the results indicate that neutrinos from the bubbles could be discovered in about one year of operation, for a neutrino spectrum with a cutoff at 100 TeV and a detector with about 6 km(3) of instrumented volume. The effect of a possible lower cutoff is also considered. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino telescope; Fermi Bubbles; KM3NeT